Prosze o pomoc jakiegoś geniusza bo mi coś nie wychodzi,a przecież się staram;)

Rozwiąż nierówność:
a) (5-√3)x>1
b) (√3-5)x>1
c) 1-√3x>x+5
d) 2+√5x>2x-3
e) (√3-1)(√3+1)x≥4√3x-10
f) x-π≥xπ
g) πy-2<3y+4


DZIĘKUJE:-)

1

Odpowiedzi

  • Użytkownik Zadane
2009-05-27T17:49:28+02:00
(5-√3)x>1
x>1/(5-√3)

(√3-5)x>1
x<1/(√3-5) bo (√3-5) jest liczbą ujemną √3-5≈1,7-5≈-3,3


c) 1-√3x>x+5
-√3x-x>4
-x(√ 3+1)>4
x<-4/(√ 3+1)

2+√5x>2x-3
√5x-2x>-5
x(√5-2)>-5
x>-5/(√5-2)


(√3-1)(√3+1)x≥4√3x-10
(3-1)x-4√3x≥-10
x(2-4√3)≥-10
x≤-10/(2-4√3)

x-π≥xπ
x-πx≥π
x(1-π)≥π
x≤π/(1-π)

πy-2<3y+4
πy-3y<4 +2
y(π-3)<6
y<6/(π-3)